RADIKALISASI PETANI MUSLIM DALAM PERSPEKTIF SOSIOLOGIS - Mawardi J, M. (Analisis: Jurnal Studi Keislaman, 2015)
The emergence of the Peasant radicalism is not caused by any defect in the social structure, but because the process of exploitation  and domination of one class against another. The Peasant radicalism is understood as a reaction of the proletariat against the bourgeoisie, is an expression  of a contradictory  class structure.  The  Socio- economic deprivation and the political repression of the state and economic power market  / capitalism  is a factor  that  grows and develops exclusivism resistance. Moreover when there are agrarian policies that harm the interests  of the farmers, both in accessing and in the mastery of agrarian resources (land), will give birth to an increasingly harsh peasant resistance, militant,  emotional and destructive.  The radicalism done by farmers Muslim community, makes  the  religion  fanaticism  as a movement  ideology  and an inspiration source as well as the value used in constructing communalism,  even they are able to construct  radicalism  using religious symbols as edging actions  taken thus further motivate and mobilize the resistance.  Nevertheless  resistance  farmers led by warsidi failures, even appearing new stigma as the movement of security meddler who want to establish an Islamic state.